KLF5/MDM2 Axis Modulates Oxidative Stress and Epithelial-Mesenchymal Transition in Human Lens Epithelial Cells: The Role in Diabetic Cataract - Li, Xiao; Chen, Doudou; Ouyang, Bowen; Wang, Shengnan; Li, Yawei; Li, Li; Zhu, Siquan; Zheng, Guangying (Laboratory investigation, 2023)
Diabetic cataract (DC) is a common cause of visual loss in older diabetic subjects. Krüppel-like factor 5 (KLF5) plays an essential role in migration and the epithelial-mesenchymal transition (EMT) in diverse cells and is involved in oxidative stress. However, the effects of KLF5 on DC remain unknown. This study aimed to examine the biological function of KLF5 in DC and its underlying mechanism. The expression patterns of KLF5 were detected in vivo and in vitro. Then, KLF5 was knocked down in human lens epithelial cells (HLECs) to explore its functional roles and underlying mechanisms. Dual-luciferase reporter assay and chromatin immunoprecipitation analysis were used to detect whether KLF5 could bind the promoter of E3 ubiquitin ligase mouse double minute 2 (MDM2), a key regulator of EMT. Lastly, the regulation of KLF5 in the biological behaviors of HLECs via MDM2 was analyzed. We found a significant increase of KLF5 in the DC lens anterior capsular, diabetic rat lens, and high glucose (HG)-stimulated HLECs. Knockdown of KLF5 inhibited oxidative stress, inflammation, migration, and EMT of HG-stimulated HLECs. KLF5 silencing impeded MDM2 expression and restricted the activation of MARK1/FAK and NF-κB signaling pathways in HLECs under HG condition. Additionally, KLF5 was found to bind the MDM2 promoter and enhance the transcriptional activity of MDM2. The protective effects by silencing KLF5 on HG-cultured HLECs could be offset by MDM2 overexpression. We demonstrated that knockdown of KLF5 alleviated oxidative stress, migration, and EMT of HG-cultured HLECs by regulating MDM2, suggesting a potential therapeutic strategy for DC.